2020
DOI: 10.29333/iejme/9292
|View full text |Cite
|
Sign up to set email alerts
|

A Suggestion of a Framework: Conceptualization of the Factors That Affect Technology Integration in Mathematics Education

Abstract: The aim of this study is to identify the main factors that affected the process of technology integration in mathematics education. The methodological approach taken in this study is a structured grounded theory. The participants of the study included two secondary-school mathematics teachers, four students selected by the teachers, and two school administrators who were responsible for technology implementation. The data collection tools included two semi-structured interview forms based on a literature revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It was first introduced by Finn in the 1960s under the concept of instructional technology. Since then, related concepts have been introduced, such as educational technologies, information technologies, and information and communication technologies (Ince-Muslu & Erduran, 2021). We are now in the final phase of it -Technology Integration, which is referred to the incorporation of technology and technology-based practices into all teaching and learning-related activities (Wachira & Keengwe, 2011, as cited in Ince-Muslu & Erduran, 2021.…”
Section: Technology Integration In Teaching Mathematicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was first introduced by Finn in the 1960s under the concept of instructional technology. Since then, related concepts have been introduced, such as educational technologies, information technologies, and information and communication technologies (Ince-Muslu & Erduran, 2021). We are now in the final phase of it -Technology Integration, which is referred to the incorporation of technology and technology-based practices into all teaching and learning-related activities (Wachira & Keengwe, 2011, as cited in Ince-Muslu & Erduran, 2021.…”
Section: Technology Integration In Teaching Mathematicsmentioning
confidence: 99%
“…While mathematics education has significant implications for STEM education in general, the mathematics curriculum needs a reform that brings teaching and learning to a whole new level. Technology integration in teaching and learning mathematics helps develop critical and scientific thinking (Das, 2019), improve analytical and problem-solving skills (Mulenga & Eickelmann, 2017, as cited in Kek & Maat, 2020), and facilitate interpretation of mathematical concepts (Ince-Muslu & Erduran, 2021). Given the significance of maths, educational leaders are expected to play essential roles in improving maths teaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides knowledge, Clark-Wilson and Hoyles (2019, p.347) also considered a teacher's personal orientations in terms of affective variables, i.e., "goal, attitudes, dispositions, beliefs, values, tastes, and preferences" in their "Technological Pedagogical Content Knowledge" model. All these three models cover most parts of the ZPD, and a few parts of the ZFM and ZPA, and posit the factors affecting integration of technology as echoed in the study of Ince-Muslu and Erduran (2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the benefits of ICT integration in mathematics education, studies from developing countries have shown that few teachers are truly integrating ICT into mathematics instruction (Agyei & Voogt, 2011). This calls for constant investigation into the factors that might positively influence such teachers' adaptation of ICT in the teaching and learning of mathematics (Ince-Muslu & Erduran, 2020;Perienen, 2020). However, factors such as teachers' pedagogical beliefs, computer anxiety, and attitudes of teachers have been considered crucial hurdles to ICT integration in education (Ruiz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%